Notifications and Health Consequences of Unauthorized Pharmaceuticals in Food Supplements - Maja Amidžić; Jelena Banović Fuentes; Jovica Banović; Ljilja Torović (MDPI AG, 2023)
Health concerns associated with the consumption of food supplements rise in parallel with the rise in the popularity and market availability of these products. In pursuit of data related to the unauthorized presence of pharmaceuticals in food supplements, the Rapid Alert System for Food and Feed (RASFF) database was searched for the 2011-2022 period. The most "popular" pharmaceuticals for the adulteration of food supplements were phosphodiesterase-5 inhibitors (235 records); anorexics and laxatives (76), including sibutramine and its active metabolite N-didesmethyl sibutramine, phenolphthalein and 2,4-dinitrophenol; stimulants, among which 1,3-dimethylamine (97), and synephrine (53) were the most numerous; nootropic drugs (24); anabolics and prohormones (16); and cannabinoid cannabidiol (14) (pending authorization as a novel food ingredient). Over 65% of notifications of interest were classified as serious risks, and over 80% of these were alert or border rejection notifications, mainly generated as a result of official control on the market. The alarming number of RASFF notifications should be considered a public health issue, demanding clear and targeted recommendation for action for the legislature and authorities. A harmonized nutrivigilance system should be considered as a tool to detect and scrutinize the adverse health effects of food supplements, along with measures to improve their safety, quality, and testing.